314PAn EGF motif of Del1 inhibits efficient angiogenesis and suppresses tumour growth in vivo. (24th November 2019) - Kitano, H; Mamiya, A; Masaoka, Y; Hidai, C
Abstract: Background: Recently, the gene therapy is attacked attention for a new cancer therapy. We invented for cancer gene therapy by a Del1 fragment. Del1 protein is composed of five domains, including three epidermal growth factor (EGF) repeats (E1–E3) and two discoidin domains (C1, C2). It consists of E2 has been reported to contain an RGD sequence that binds to integrin receptors and supports endothelial cell survival. The C1 domain is essential for the deposition of Del1 in the ECM. Additionally, the E3 domain can increase transfection efficiency. The Del1 protein was deposited in ECM, increased apoptosis, and enhanced the efficiency of a following transfection.At high concentrations, E3 induces apoptosis. And more, Dell is known to show pro-angiogenic or anti-angiogenic activities depending on the experimental conditions. In the present study, mouse ex-planted tumors were treated with the Del1 protein by a non-viral vector. Methods: Cells of the human oral squamous cell carcinoma cell line, SCCKN, were injected into nude mice to generate explanted tumors. cDNAs encoding, the E3 and C1 domains of Del1 (E3C1), were inserted into pcDNA3D (pE3C1)and injected into the tumors every 7 days with a transfection reagent, jet-PEI. Tumor angiogenesis was evaluated by immunohistochemistry with antibodies for PECAM, von Willebrand factor and PDGF-beta and intravenous injection of lycopersicon esculentum lectin. The signal transduction of Notch was analyzed by western blotting. Results: Treatment with pE3C1 suppressed the growth of explanted tumors and improved life prognosis of mice. In localization with immunostaining of PECAM or von Willebrand factor, and angioglaphy with lycopersicon esculentum lectin, vasculature without lumen were increased by gene therapy of Del1 fragment. Among the treatment with pE3C1 and control, the PDGF beta staining cells, which is marker of tip cells in angiogenesis, were increased. Western blotting of human umbilical endothelial cells cultured with an E3C1 recombinant protein showed the decreased expression of active Notch and hey1. Conclusions: In the present study, we provide evidence that an E3C1 fragment suppresses Notch signaling and angiogenesis in explanted tumor model. Legal entity responsible for the study: Hisataka Kitano. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.